GENE-17. ATRX LOSS IN GLIOMA RESULTS IN EPIGENETIC DYSREGULATION OF THE G2/M CHECKPOINT AND SENSITIVITY TO ATM INHIBITION. (11th November 2019) - Mullan, Brendan; Qin, Tingting; Siada, Ruby; Ravindran, Ramya; Garcia, Taylor; Muruganand, Ashwath; Harris, Micah; Danussi, Carla; Brosnan-Cashman, Jacqueline; Pratt, Drew; Zhao, Xinyi; Rehemtulla, Alnawaz; et al.
Abstract: Gliomas are a leading cause of cancer mortality in children and adults and new targeted therapies are desperately needed. ATRX is a chromatin remodeling protein that is recurrently mutated in H3F3A -mutant pediatric GBM and IDH -mutant grade 2/3 adult glioma. We previously showed that loss of ATRX in glioma results in tumor growth and additional tumor mutations. However, the mechanism driving these phenotypes has not been fully established. We found that in ChIP-Seq datasets of mouse neuronal precursor cells (NPCs) and experimental models of human glioma cells, ATRX binds and regulates the chromatin state of promoters and enhancers for gene sets associated with regulation of the cell cycle G2/M checkpoint. In line with this, analysis of single-cell seq (sc-seq) data from IDH-mutant gliomas (n=16) shows that ATRX-mutant tumors (IDH-A) demonstrate a population of cycling cells with dysregulated cell cycle phase gene set expression when compared to ATRX-wildtype tumors (IDH-O). In glioma models, ATRX-deficient cells exhibit a seven-fold increase in mitotic index at 16 hours after sub-lethal radiation and enhanced activation of the master cell cycle regulator ATM with radiation. Treatment of ATRX-deficient gliomas with ATM inhibitors results in a selective increase in dysfunctional cell cycling and increased radio-sensitization in ATRX-deficient glioma cells. Using an ATM-luciferase reporter in orthotopically-implanted human GBM cells, both AZD0156 and AZD1390 demonstrate in vivo pathway inhibition. Mice intra-cranially implanted with ATRX-deficient GBM cells demonstrate a doubling of median survival compared to radiated controls (p=0.0018) when treated with AZD0156 combined with radiation. This study demonstrates that ATRX-deficient glioma display epigenetic dysregulation of the G2/M checkpoint, which opens a new window for therapies targeting this unique phenotype.